Longitudinal associations between intake of fruit and vegetables and height attainment from preschool to school entry - Rosário, Rafaela (2021)
To examine associations between fruit and vegetable intake in young childhood and height attainment during preschool and at school entry. Data for this study was based on “The Healthy Start” primary intervention study, which included 635 obesity-prone children, (58% boys), from the greater Copenhagen area, with a mean (SD) age of 4.0 (1.1) years (age range 2–6 years) at baseline. In the current study, 553 children (57% boys) were included with information on dietary intake at baseline and height measured at baseline (preschool age), and 511 children (56.8% boys) with the height measured at school entry (~6 years old). Height was measured by trained health professionals during the intervention and by school nurses at school entry. Information on intakes of fruit and vegetables, separately and combined, was gathered with four-day dietary records reported by parents. Participants were grouped into tertiles for their intakes at baseline. Compared to boys with low consumption, those with a moderate and high intakes of fruit and vegetables (F&V) had a greater attained height at preschool of 1.3 cm (95% confidence interval (CI): 0.3; 2.3) and at school entry of 2.4 cm (95% CI: 0.8; 3.9) and 1.8 cm (95% CI: 0.2; 3.4), respectively, also after adjustment for differences in age, body mass index (BMI), and total energy intake. Additional adjustment for mid-parental height and parents’ education did not alter the significant associations between moderate consumption of F&V and attained height at preschool and school entry. There was no association among girls. Our results showed that a moderate consumption of F&V was directly associated with higher attainment in height at preschool and school entry in boys. From a public health perspective, it should be prioritized to continue developing intervention programs to improve fruit and vegetable intake.